Assessing the energy dynamics of Pakistan: Prospects of biomass energy - Muhammad Irfan; Zhen-Yu Zhao; Manoj Kumar Panjwani; Fareed Hussain Mangi; Heng Li; Ali Jan; Munir Ahmad; Abdul Rehman (Energy Reports, 2020)
The energy needs of Pakistan have increased many folds in recent years due to improved lifestyle, ever-increasing population, and economic development. Biomass energy has emerged as a promising renewable energy source and has an enormous potential to fulfill the energy requirements of the country. This paper aims to assess the current situation and future projections of electricity generation by using biomass energy resources. For this purpose, we critically reviewed extensive literature i.e., research papers, energy reports, official statistical data, relevant regulations, and government policies. Research findings reveal that the abundant biomass resources of the country include fuelwood, agricultural residues, animal dung, and municipal solid waste. 48% of the domestic energy needs are being fulfilled from fuelwood, while another 32% by crop and animal residues. 85 sugar industries of the country produce enough bagasse to generate 5800 GWh of electricity. Corn stalk, sugarcane trash, rice straw, wheat straw, and cotton stalks are the major crop residues having a production of 6.43, 8.94, 17.86, 35.6, and 50.6 Mt, respectively. The power generation potential from animal dung is 4800-5600 MW. Similarly, the electricity generation potential of municipal solid waste by thermochemical and biochemical conversion is 560 kWh/t and 220 kWh/t, respectively. As envisioned by the Pakistani government to enhance the share of renewables in the total energy mix of the country from 1.1% to 5% by 2030, biomass energy has high prospects to achieve this target.
Keywords: 330; Biomass energy; Energy dynamics; Fuelwood; Animal dung; Crop residues; Municipal solid waste; Pakistan